44.9k views
8 votes
Evaluate the expression when y = -6

Y2+5Y-3

User Chinjoo
by
5.3k points

2 Answers

7 votes

Answer:

Solve the equation for Y by finding a , b , and c of the quadratic then applying the quadratic formula. Y = − 5 − √ 97 + 24 y 12 Y = − 5 + √ 24 y + 97 12

User William Durand
by
5.3k points
10 votes

Answer:

-45

Explanation:

(-6)2+5(-6)-3=-45

User Adeina
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.